(untitled) (Acta Scientiarum. Animal Sciences, 2020)
The objective of this study was to evaluate dry mass production, fermentative parameters and chemical and bromatological composition of sunflower silage and Paiaguas palisadegrass silage in monocropped and intercropping in different forage systems. The experimental design consisted of randomized blocks, with four replicates. The treatments consisted of silage forage systems: sunflower monocropped; Paiaguas palisadegrass monocropped; sunflower row-intercropped with Paiaguas palisadegrass; sunflower inter-row intercropped with Paiaguas palisadegrass; and sunflower oversown and intercropped with Paiaguas palisadegrass, totalizing 20 experimental silos. Sunflower and Paiaguas palisadegrass were harvested at 110 days after planting at 20 cm from the soil for silage, using brush cutter. The silos were opened after 53 days of fermentation. The rows and inter-row intercropped systems contributed to increase the mass production of the ensiled material. The monocropped sunflower silage had higher values of pH, ethereal extract and acid detergent fiber and lower values of titratable acidity and dry matter, crude protein, neutral detergent fiber and in vitro dry matter digestibility values. The silages of the sunflower intercropped with Paiaguas palisadegrass in forage systems of crop-livestock integration presented better fermentative and bromatological characteristics, guaranteeing an adequate fermentative process and nutritional quality. In this way, the intercropping of these two forages potentiates the production of silage for feeding of ruminants during the period of forage shortage.